Is shared learning the way to bring UK neurology and psychiatry closer: what teachers, trainers and trainees think. Issue 8 (20th March 2006) - Schon, F; MacKay, A; Fernandez, C
Abstract : Background: Rapid advances in brain sciences are challenging the validity of the traditional divide between neurology and psychiatry. The need for closer ties has been widely advocated. Objective: To assess attitudes of neurologists and psychiatrists to closer links in general and to joint education in particular. Methods: Postal questionnaire survey of trainees (SpRs) trainers (Members of Special Advisory Committees in Neurology and General and Old Age Psychiatry) and teachers (Undergraduate coordinators). Analysis based on 55 neurology and 50 psychiatry respondents. Results: 5 general attitude questions on links showed most respondents "keen" on links and "unkeen" on current separation of disciplines. 15 topics possibly suitable for joint teaching were offered. 7 were rated between "keen" and very "keen" with maximum support for somatization, dementia, chronic pain and pharmacology. 7 were rated positively, only eating disorders was felt unsuitable. 6 options were offered for joint training opportunities. Trainees were keen on attending joint education, clinical and patient management sessions and outpatient clinics. Psychiatrists were even keener on links than neurologists with psychiatric SpRs significantly more in favour of certain items. Conclusions: The survey found widespread support from trainees, trainers and teachers for closer links. Trainees were keen to attend joint clinically focussed sessions. Psychiatrists tended to be keener that neurologists on links. This survey should encourage the establishment of closer educational links at all levels.